Implementation of Ward and Peppard in Information Systems Strategic Planning (Case Study: Hotel Kartika Bandungan) - Desyana, Natasya Putri; Sitokdana, Melkior N. N. (Journal of Information Systems and Informatics, 2022)
Hotel Kartika Bandungan is one of the family hotels located in Bandungan District, Semarang Regency, Central Java Province. Hotel Kartika Bandungan has a lag in the field of technology because other hotels around it already have their own system. Due to the absence of an integrated system, it is necessary to plan an IT / SI strategic plan that suits the needs and conditions of the Kartika Bandungan Hotel. This study aims to increase the effectiveness and efficiency in carrying out business processes, as well as make Hotel Kartika Bandungan still able to lead during hospitality business competition. In this study, the methodology used was Ward and Peppard which was supported by SWOT, PEST, Value Chain and McFarlan Strategic Grid analysis methods. The data collection method used is a descriptive qualitative method inandi by conducting an interview with the company owner and direct observation to the Kartika Bandungan Hotel. Based on the results of the analysis at the Kartika Hotel Bandungan, it is proposed that the Customer Data Information System, Financial Information System, Employee Payroll Information System, Hotel Needs Information System, and Attendance Information System are proposed. The results of IT/SI strategic planning can be implemented in the next four years.
Keywords: Strategic Planning, Information Systems, Ward and Peppard